2021
DOI: 10.1002/leap.1404
|View full text |Cite
|
Sign up to set email alerts
|

Home country bias in academic publishing: A case study of the New England Journal of Medicine

Abstract: This study examined home country bias in the New England Journal of Medicine (NEJM). Bibliographic information of publications in the NEJM from 2000 to 2019 was collected as data. Bibliometric analyses were performed to investigate the number of papers with one or more US‐based authors in the NEJM and compare this to other journals. Citation counts of US‐based and non‐US papers were calculated and compared. The results show that US‐based papers account for 65.44% of the NEJM papers, and the US share of the NEJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Last, we extracted the raw citation counts received by each paper from the downloaded bibliographic information. To make papers from different years comparable in research impact, we normalized the citation counts with Formula 2 following the approach of previous studies (Wei & Lei, 2018 ; Zhu, 2021 ). …”
Section: Methodsmentioning
confidence: 99%
“…Last, we extracted the raw citation counts received by each paper from the downloaded bibliographic information. To make papers from different years comparable in research impact, we normalized the citation counts with Formula 2 following the approach of previous studies (Wei & Lei, 2018 ; Zhu, 2021 ). …”
Section: Methodsmentioning
confidence: 99%
“…Third, we searched bibliographic data from three sub-databases of WoS: Science Citation Index Expanded (SCIE), Social Sciences Citation Index (SSCI), and Arts & Humanities Citation Index (A&HCI). WoS was chosen as the data source because it is arguably one of the most famous and comprehensive databases of bibliographic information in the world (Song et al, 2019), and it has been widely utilized in many previous studies (Cansun & Arik, 2018; Raban & Gordon, 2020; Zhang et al, 2020; Zhu, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, to capture the temporal change in research productivity (e.g., the annual trends of TC-related publication counts), we applied the Mann-Kendall trend test, a recommended method for non-parametric time series analysis (Kisi & Ay, 2014; Zhu, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…However, prior empirical studies have reported editorial biases associated with factors such as gender, race, country of origin, reputation and institutional affiliation in the gatekeeping practices of academic journals worldwide (Cameron et al, 2016; De Oliveira et al, 2012; Moustafa, 2015; Zhu, 2021). For example, the fame of academics has been shown to play a significant role in how favourably their work is received by journals (Bravo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Since journal editors serve as the gatekeepers of the publishing process by deciding whether a submission is sent out for external peer review and is publishable thereafter (Grace, 2004), they are generally expected to evaluate and accept articles based solely on the merit of the authors' academic writings and the novelty of their research. However, prior empirical studies have reported editorial biases associated with factors such as gender, race, country of origin, reputation and institutional affiliation in the gatekeeping practices of academic journals worldwide (Cameron et al, 2016;De Oliveira et al, 2012;Moustafa, 2015;Zhu, 2021). For example, the fame of academics has been shown to play a significant role in how favourably their work is received by journals (Bravo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%